(untitled) (Comprehensive Journal of Science, 2025)
The current study aimed to explore human resource management and development in governmental organizations, with a specific focus on the Ministry of Technical and Vocational Education in. The researcher employed the descriptive-analytical method, using a questionnaire as the primary tool for data collection. The sample consisted of 150 employees working within the ministry. The findings revealed that human resource management and development are of high importance within the ministry. Dimensions related to incentives and training recorded the highest mean scores, reflecting participants’ awareness of their impact on HR development. The results also highlighted the significant role of human resource planning, while recruitment and selection ranked lowest in perceived importance, though they remain influential in performance improvement. Moreover, the study emphasized the central role of training in enhancing skills and competencies, as well as the importance of incentives in boosting morale and improving performance. Performance appraisal was also identified as a key tool in identifying training and development needs. Finally, the results indicated that the overall level of human resource development within the ministry is high, with a clear positive impact on the quality of organizational performance.